2011
DOI: 10.5551/jat.5215
|View full text |Cite
|
Sign up to set email alerts
|

Serum Low-Density Lipoprotein to High-Density Lipoprotein Ratio as a Predictor of Future Acute Myocardial Infarction Among Men in a 2.7-Year Cohort Study of a Japanese Northern Rural Population

Abstract: Aim: To examine and compare the predictive value of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), TC/HDL-C and LDL-C/HDL-C ratios for future cardiovascular outcomes in the general Japanese population. Methods: A total of 24,566 eligible participants aged 18 years or older, without cardiovascular disease, were enrolled through multiphase health screening and divided into quartile groups based on lipoprotein levels or ratios. Primary endpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 30 publications
3
59
2
Order By: Relevance
“…Recent studies conducted in Japan have suggested the L/H ratio as a predictor of clinical outcomes in patients after percutaneous coronary intervention, 33 and in the general population. 34 Functional improvement observed in the present study corresponded well with the recent finding by Otagiri et al, 35 who found beneficial vascular structural changes, including a significant reduction of lipid components of the coronary plaque, in Japanese patients with ACS following early administration of low-dose rosuvastatin (2.5 mg/day up to 5 mg/day) for 6 months. In Protocol 2, all patients who had been switched from usual-dose fluvastatin to rosuvastatin attained the target LDL-C level at 12 months after the switch.…”
Section: Other Drugssupporting
confidence: 81%
“…Recent studies conducted in Japan have suggested the L/H ratio as a predictor of clinical outcomes in patients after percutaneous coronary intervention, 33 and in the general population. 34 Functional improvement observed in the present study corresponded well with the recent finding by Otagiri et al, 35 who found beneficial vascular structural changes, including a significant reduction of lipid components of the coronary plaque, in Japanese patients with ACS following early administration of low-dose rosuvastatin (2.5 mg/day up to 5 mg/day) for 6 months. In Protocol 2, all patients who had been switched from usual-dose fluvastatin to rosuvastatin attained the target LDL-C level at 12 months after the switch.…”
Section: Other Drugssupporting
confidence: 81%
“…The predictability of future CVD events has been well assessed in previous epidemiological studies of the general population 15,16) . These studies demonstrated the high reliability of HDL-C in predicting future CVD, and ratios incorporating HDL-C showed greater predictability of CVD than LDL-C or TG alone.…”
Section: Discussionmentioning
confidence: 99%
“…Italy, China, and Japan), baseline population risk appears to be unusually low (Menotti et al 1993;Campbell et al 1998;Yokokawa et al 2011). This may be due in part to a lifetime of relatively low LDL-C levels, but other poorly defined factors likely account for the low population risk.…”
Section: Risk Assessment By Atherosclerosis Imagingmentioning
confidence: 99%